2014
DOI: 10.1021/jp412053w
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Probing of Receptor–Nanoparticle Interactions for Riboflavin Receptor Targeted Gold–Dendrimer Nanocomposites

Abstract: Riboflavin receptors are overexpressed in malignant cells from certain human breast and prostate cancers, and they constitute a group of potential surface markers important for cancer targeted delivery of therapeutic agents and imaging molecules. Here we report on the fabrication and atomic force microscopy (AFM) characterization of a core–shell nanocomposite consisting of a gold nanoparticle (AuNP) coated with riboflavin receptor-targeting poly(amido amine) dendrimer. We designed this nanocomposite for potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 78 publications
0
32
0
Order By: Relevance
“…Furthermore, the RF-targeted dendrimer conjugate (N-10 position) was used to coat gold nanoparticles (AuNP) [76]. The AuNP were prepared by the gold (III) reduction method and had a hydrodynamic size of 30 nm according to dynamic light scattering (DLS), while atomic force microscopy (AFM) showed a 13.5 nm core diameter.…”
Section: Dendrimersmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the RF-targeted dendrimer conjugate (N-10 position) was used to coat gold nanoparticles (AuNP) [76]. The AuNP were prepared by the gold (III) reduction method and had a hydrodynamic size of 30 nm according to dynamic light scattering (DLS), while atomic force microscopy (AFM) showed a 13.5 nm core diameter.…”
Section: Dendrimersmentioning
confidence: 99%
“…The dendrimer conjugates were attached to the AuNP via gold-sulfur chemisorption and had a size of 20.5 nm measured by AFM. The uptake of AuNP-PAMAM-RF was tested in KB cells [76]. According to surface plasmon resonance (SPR) and luminescence of AuNP, the RF-targeted nanocomposite showed higher internalization into cells than the control.…”
Section: Dendrimersmentioning
confidence: 99%
“…Freshly cleaved mica was modified with a 100 L deposit of 0.01% 3-(aminopropyl)triethoxysilane (APTES) solution. After a 20 min incubation period, the mica surface was rinsed six times with 1 mL aliquots of water and dried with compressed nitrogen [25]. A drop of 10 L suspension of AuNPs without and with dimethoate was deposited on mica surface and incubated for 30 min, followed by repeated washing with deionized water to remove any unbound materials and dried in air for AFM measurements [26].…”
Section: Characterization Of Aunps and Their Dimethoate Conjugatesmentioning
confidence: 99%
“…Previous reports [32][33][34][35][36][37][38][39][40] showed that BP can induce cell death of certain cancer cells through apoptosis. When cancer cells respond to apoptotic stimuli, the nerve growth factor IB, that is, Nur77, translocates from the nucleus to the mitochondria, where it binds to B-cell lymphoma 2.…”
Section: Introductionmentioning
confidence: 98%
“…Angelica sinensis (Danggui), a common Chinese medicinal herb, has been used to promote blood circulation [29] to treat female menstrual disorders [30] and menopausal symptoms [31]. n-Butylidenephthalide (BP) is one of the active ingredients of A. sinensis with potential in treating multiforme [32][33][34][35], breast cancer [32], prostate cancer [36,37], oral squamous cell carcinoma [38], lung cancer [39] and hepatoma [40].…”
Section: Introductionmentioning
confidence: 99%